The relationship between personality and behavioural traits and entrepreneurs' competitiveness / Dr Oriah Akir, Dr Tang Howe Eng and Senian Malie. - Akir, Oriah (Dr); Tang, Howe Eng (Dr); Malie, Senian (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2016)
This study explores the elements of personality and / or behavioural traits that explain the entrepreneurs' competitiveness; and come out with an extended model in addition to the existing body of knowledge relating to the field of entrepreneurship and entrepreneurs. Cross-sectional survey design is carried out to determine the best competitive entrepreneurial behaviourial model. The findings indicated that proactive trait made the largest contribution in explaining a competitive entrepreneur (β = 0.420, p = 0.000), next largest contributing factor was innovative (β = 0.286, p = 0.000), followed by networking (β = 0.103, p = 0.002), and then risk taking (β = 0.098, p = 0.018). This study also explores the motivating, success and challenging factors experienced by entrepreneurs in their business ventures. In conclusion, this study has the potential inputs and insights to managerial and decision-makers in sponsoring the financial / capital assistance to new entrepreneurs or even existing one to assess their capability, feasibility and the future growth of their business ventures.